READING MUHAMMAD ARKOUN'S THOUGHT ON THE DISCOURSE OF CONTEMPORARY QUR'ANIC STUDIES: An Introduction to the Study of QS. Al-Fatihah [1]: 1-7 - Al Jufri, Muhammad Arman (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2021)
This paper is a reading of the offer that Muhammad Arkoun has given in the development efforts in the study of the Qur'an in the Contemporary era. Muhammad Arkoun's fundamental disharmony lies in the fact that the reality of society has completely changed, and therefore, requires a new model of reading authoritative religious texts, namely the Qur'an and Hadith. The methodological offers made by classical Islamic thinkers, in the view of Muhammad Arkoun, are considered no longer able to answer the problems of today's society. The majority of them are still often caught up in religious dogmatic pairings. To solve this problem, Muhammad Arkoun offered three models of rereading the Qur'an, namely with linguistic, anthropological, and historical approaches. The results of these three offers of reading of the Qur'an will lead to the results of interpretations relevant to the needs of people living in contemporary reality.